Structure-performance relationship in CuO/SBA-15-type SOx adsorbent: evolution of copper-based species under different regenerative treatments. Issue 18 (30th August 2017) - Berger, M.; Fioux, P.; Dorge, S.; Nouali, H.; Habermacher, D.; Fiani, E.; Vierling, M.; Moliere, M.; Brilhac, J. F.; Patarin, J.
Abstract : Desulfurization of industrial flue gas stream: characterization of the evolution of copper active sites along SO x adsorption/regeneration cycling experiments in CuO/SBA-15-type adsorbent. Abstract : Sulphur oxides (SO x ) represent a major air pollutant and are controlled by national and international regulations. CuO/SiO2 materials are known as SO x trap materials. However, their large-scale development is still hampered by the sintering of the active phase over multiple adsorption/regeneration cycles, leading to the progressive decrease in SO x adsorption capacities of the adsorbent. In this work, SBA-15 organised mesoporous silica was functionalized with highly dispersed Cu 2+ -based species. The as-obtained adsorbent was then assessed as a regenerable SO x trap material. An extended characterisation was performed along with adsorption/regeneration cycles to correlate the evolution of the copper species with the performance of the adsorbent under different regenerative treatments. Thermal regeneration at 600 °C under pure N2 leads to the formation of Cu + -based species, enabling a significant increase in SO x chemisorption efficiency, which nevertheless decreases during the subsequent cycles due to progressive sintering of the active phase, leading to bulky copper(ii ) oxide particles. Regeneration under reductive conditions (0.5 vol% of H2 in N2 ) was then investigated as a way to decrease the regeneration temperature and limit this sintering process. It was found that the general behaviour of the copper-based species was very sensitive to the regeneration temperature. At 600 °C, the active phase was completely converted into large metallic copper particles, giving rise to a fast decrease in SO x adsorption capacity of the adsorbent due to partial obstruction of the SBA-15 silica porosity. Conversely, when this regeneration was performed at 280 °C, no decrease in performances was noticed, and the copper species remained as a highly dispersed phase on the silica support.